Hubungan Bullying dengan Kepercayaan Diri Siswa-Siswi - Nuraini, Meillisa; Syafitri, Aisyah; Agustina, Marisca (MPI Press, 2023)
Introduction: The problem of bullying turns into an endless risk. Bullying continues to grow consistently and is increasingly common in school settings. Bullying is a threat that a person makes to others to cause psychological disturbances for his victims. Bullying that occurs can be in the form of verbal, physical, rational, and cyberbullying. Students who get bullying behavior from their friends can affect their confidence. Objectives: This study aims to determine the relationship between bullying and self-confidence in students at SMP Triguna Depok. Method: In this study, researchers used a correlation descriptive design with a cross-sectional approach with a sample of 74 respondents using total sampling techniques. The instruments used were an olweus bullying questionnaire and a confidence questionnaire. Statistical tests use the chi-square statistical test. Result: The results of the study using a chi-square statistical test of the relationship between bullying and self-confidence in students at SMP Triguna Depok obtained p-value = 0.000 < 0.05. Conclusion: There is a relationship between bullying and self-confidence in students at SMP Triguna Depok in 2022.